2021
DOI: 10.1101/2021.10.26.465874
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Patient-derived zebrafish xenograft models reveal ferroptosis as a fatal and druggable weakness in metastatic uveal melanoma

Abstract: Uveal melanoma (UM) is the most common intraocular melanoma, derived from transformed melanocytes of the uvea. Although treatment of primary UM is usually successful, there is a high risk (up to 50%) of liver metastasis with negligible long-term survival. There are currently no reproducible patient-derived animal models that faithfully recapitulate the latter stages of metastatic dissemination of UM, hindering the discovery of curative treatments. To overcome this problem and to accelerate the development of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…The drug efficacy obtained in this proof-of-concept experiment in the zf-PDX model recapitulated published results using UM cells and the murine PDX model [38]. Our recent study harnessing this model identified ferroptosis as a new and druggable pathway for the treatment of UM patients [34]. In another group, Glinkina et al also tested target agent combinations with the zf-PDX UM model but did not detect tumor regression [44].…”
Section: Combination Treatment With Navitoclax and Everolimus Validat...supporting
confidence: 80%
See 1 more Smart Citation
“…The drug efficacy obtained in this proof-of-concept experiment in the zf-PDX model recapitulated published results using UM cells and the murine PDX model [38]. Our recent study harnessing this model identified ferroptosis as a new and druggable pathway for the treatment of UM patients [34]. In another group, Glinkina et al also tested target agent combinations with the zf-PDX UM model but did not detect tumor regression [44].…”
Section: Combination Treatment With Navitoclax and Everolimus Validat...supporting
confidence: 80%
“…Next, we validated the biological properties of the patient-derived UM spheroids (Figure 2a,b). Our previous study indicated that the culturing of UM tissue as spheroids helped to preserve the expression of melanocyte-specific antigen (melan-A) and their intrinsic tumorigenic capacity [34]. Here, we determined the melanocytic origin of the cultured spheroids using the melanocyte marker SOX10 (Sry-related HMG-Box gene 10) (Figure 2b).…”
Section: Short-lived Patient-derived Um Spheroids Maintain Their Mela...mentioning
confidence: 97%
“…Metastatic uveal melanoma cells were derived from spXmm66-tomato red spheroid cultures, as described by Groenewoud and colleagues [45]. Cells were processed into a single-cell suspension through trituration and were subsequently filtered through a 30 µm cell strainer (Miltenyi Biotec).…”
Section: Generation Of Metastatic Um-patient-derived Zebrafish Xenogr...mentioning
confidence: 99%
“…Next, we examined whether the synergistic effects of the combinations of everolimus with KU57788 or OSI-906 observed in vitro could be reproduced in vivo. For this purpose, we exploited a metastatic UM-patient-derived zebrafish xenograft model (UM zf-PDX) [45]. This model is based on 3D spheroids grown from Xmm66 metastatic UM PDX cells derived from the same original donor as the MM66cell line.…”
Section: Cc-115 Efficiently Inhibits Growth Of Um Cells In An In Vivo...mentioning
confidence: 99%
“…Antitumor activity is usually evaluated by confocal imaging of tumor fluorescence or by lysing zebrafish and counting tumor cells. [182][183][184] Common cancer types are currently studied in drug development using zebrafish models including breast cancer, 47 leukemia, 185 lung cancer, 186 and melanoma, 187 demonstrating the excellent generalizability of the zebrafish transplantation tumor model.…”
Section: Evaluation Of Drug Efficacy In New Drug Developmentmentioning
confidence: 99%